Effect of oral administration of Lactobacillus johnsonii CRL1231 on adiposity and inflammatory status of mice with metabolic syndrome - Russo, Matias Irineo (2022)
Metabolic syndrome (MS) is one of the most relevant health problems in the world due to increased consumption of high-fat diets and the consequent obesity. MS is a cluster of cardio-metabolic risk factors and comorbidities conveying high risk of both cardiovascular disease and type 2 diabetes. Comorbidities associated with MS include proinflammatory state, prothrombotic state, nonalcoholic fatty liver disease. Lactobacillus johnsonii CRL1231 (Lj) is a strain with feruloyl esterase activity which increases the release of ferulic acid (FA) in the intestine and improves the biomarkers of MS. When the AF esterified in bran fibers is released, it can exert its lipid-lowering effect. The objective of this work was to evaluate the effect of oral administration of Lj on accumulation of abdominal and hepatic fat, and inflammatory state of mice with MS induced by a high-fat diet supplemented with wheat bran (HFD+WB). Male six-week-old Swiss albino mice (n = 24) were fed for 14 weeks; they were divided into 3 groups: Control group: mice received water and normal diet; MS group: mice received water and HFD+WB; MS+Lj group: mice received suspension of Lj (dose: 108 CFU / day / mouse) and HFD+WB. The adiposity index (AI) was calculated: AI = [Fat weight / Body weight] x 100. Histopathological analysis of liver and epididymal adipose tissue (evaluation of adipocyte area) was performed. Plasma levels of AST and ALT transaminases were measured by enzymatic methods and leptin levels by immunoassay. Cytokine levels (TNF-α, IFN-γ, IL-6 and IL-10) were determined by flow cytometry. The AI was 2 times higher in MS group compared to Control group, and decreased 30% in MS+Lj group compared to MS group. Abundance of large adipocytes (4000-8000 μm2) was 9% in Control group, 57% in MS group, and it was reduced to 20% in MS+Lj group. Plasma leptin levels were 7 times higher in MS group than in Control group, and 2 times lower in MS+Lj group with respect to MS group. The levels of pro-inflammatory cytokines (TNF-α, IFN-γ, IL-6) increased in MS group compared to Control group, and decreased in MS+Lj group. The levels of anti-inflammatory IL-10 were reduced 3 times in MS group compared to Control group, but an increase of 2 times was evidenced in the MS+Lj group. Liver histology revealed steatosis in the MS group and showed a reduction in fatty infiltration in hepatocytes of the MS+Lj group. Increased levels of ALT and AST are often associated with liver damage resulting from unhealthy habits, such as a high-fat diet. Results showed that ALT and AST levels increased 2 times in MS group with respect to Control group, while MS+Lj group did not show significant differences with the Control group. According to the results obtained in this work, oral administration of Lj reduces AI, prevents hypertrophy of adipose tissue, decreases hyperleptinemia, and improves the inflammatory profile and steatosis in mice with MS fed HFD+WB.